Bound by Blame: Sentencing, Colonialism, and Fetal Alcohol Spectrum Disorder - Nussbaum, Sarah-jane (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2023)
Gladue and Ipeelee send important messages to judges, but messages that have tensions within them that reflect the broader tensions of using the criminal law system to acknowledge ongoing state involvement in discrimination against Indigenous Peoples. The heart of the tension is that the criminal law system is built around assigning individual blame. I look closely at examples of judges struggling with inadequate tools to follow the Supreme Court of Canada’s guidelines to acknowledge and redress the harmful impacts of colonialism within the constraints of their job of assigning individual blame. The result, unfortunately, is a consistent failure to recognize the Canadian state’s ongoing role in colonial oppression. This article explores these tensions in the context of a particular manifestation: the judicial practice of blaming Indigenous mothers for the fetal alcohol spectrum disorder affecting their accused sons. The analysis illuminates the depth of the tensions of a common law criminal justice system in a colonial state: in the process of sentencing Indigenous offenders living with FASD, judges both strongly contest, and subtly rely upon, harmful colonial logics. I propose that a standing to blame analysis could assist judges in identifying, and responding to, the state’s own role in causing, or being complicit in, an Indigenous individual’s experiences of injustice. When the state has played such a role, the state is not justified in blaming the individual through the criminal law. The benefit of this kind of approach is that it would highlight the inappropriateness of the state’s use of individual blame to respond to harms arising in the context of colonialism and inequality.